REVEALING THE "SWAN" SYMBOL AND SOCIAL CRITICISM IN RENDRA'S POETRY “NYANYIAN ANGSA” - Tomi Arianto (eScience Humanity Journal, 2022)
The purpose of this research aimed to reveal symbols that are often present by applying semiotic critical analysis to poetry. Nyanyian Angsa (The Swan Song) is the source of data in this analytical practice. Rendra is a writer who is familiar to the Indonesian people through his sharp lines and directly affects the social phenomenon critics. In this article, the researcher implemented Riffatere's semiotic reading theory to examine the Swan symbol in poetry. Riffatere introduces 4 things in semiotic of poetry, they are (1) poetry is an indirect expression, stating something with another meaning, (2) heuristic and hermeneutic reading (retroactive), (3) matrix, model, and variant, and (4) hypogram. By using qualitative research methods, this research focused on critical analysis of the text in poetry. The results of this analysis indicated that there are many ungrammatical expressions in poetry that could not be read heuristically reading so that the reading is done by hermeneutic reading (retroactive). Through the semiotic stages, there are two major criticisms behind the ungrammatical meaning found, namely the representation of social criticism on individuals in medical and religious institutions. The Swan symbol also refers to the Maria Zaitun character who has done forgiveness of sins.